Preparing for adolescence - Dobson, James C., 1936- (Santa Ana, Calif. : Vision House Publishers, 1978)
Speaks to adolescents about such topics as drug abuse, sex, family conflict, friendship, love, and conformity.
Keywords: Adolescence -- Juvenile literature; Teenagers -- Conduct of life; Teenagers -- Religious life; Conduct of life; Christian life